(untitled) (International Seven Journal of Multidisciplinary, 2024)
The application of art in footwear design presents a unique opportunity to enhance the well-being of children and adults with autism by incorporating controlled sensory stimuli. This approach integrates natural elements—like trees, flowers, and serene colors—into shoes, creating a calming sensory experience. Colors such as blue, green, and lilac are strategically chosen for their soothing effects, fostering emotional stability and reducing stress. Research indicates that these hues promote relaxation, with blue associated with tranquility, green symbolizing nature, and lilac evoking spirituality. The texture of the footwear plays a crucial role as well, incorporating raised patterns inspired by natural forms to provide subtle, relaxing tactile stimulation. This allows for pleasant sensory interaction, particularly for individuals sensitive to excessive stimuli. Comfort is further enhanced by the inclusion of soft, non-slip insoles that distribute weight evenly and ensure safety, especially in environments where slips may occur. Recent studies reinforce the importance of creating environments that promote calm and comfort, highlighting innovative solutions that improve quality of life for individuals with sensory challenges. The design of therapeutic gardens and the development of responsive smart clothing illustrate a growing recognition of the benefits of integrating art and nature into everyday experiences. Overall, this focus on empathetic and inclusive design reflects a societal shift toward understanding and addressing the unique needs of those with autism. By prioritizing sensory-friendly features in everyday products, the integration of art into footwear not only enhances aesthetic value but also contributes significantly to emotional and physical well-being, creating a more inclusive world.